Improving Multiplication Performance in Students with Dyscalculia Using GARISMATIKA: A Single-Subject Design - Putri, Almaida Garudea; Leonard, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study investigates the effectiveness of the GARISMATIKA method – a structured, visually based instructional approach – in enhancing multiplication skills among eighth-grade students with dyscalculia. Employing a single-subject research (SSR) design with an A-B-A structure, the intervention was conducted at SMP Negeri 9 Bogor with one male student formally diagnosed with dyscalculia. The instructional focus was on solving multiplication problems involving three-digit numbers. Data were collected through systematic observation and analyzed using visual trend analysis. The results indicated significant improvements in multiplication accuracy during the intervention phase, with performance gains sustained in the follow-up phase. These findings underscore the potential of GARISMATIKA as an effective and inclusive educational tool for addressing specific mathematical learning disabilities and support its broader implementation in differentiated mathematics instruction within inclusive classroom settings. Abstrak: Studi ini mengkaji efektivitas metode GARISMATIKA—suatu pendekatan instruksional yang terstruktur dan berbasis visual—dalam meningkatkan keterampilan perkalian di antara siswa kelas delapan yang memiliki diskalkulia. Menggunakan desain penelitian subjek tunggal (SSR) dengan struktur A-B-A, intervensi ini dilaksanakan di SMP Negeri 9 Bogor dengan satu siswa laki-laki yang secara resmi didiagnosis memiliki diskalkulia. Fokus instruksional terletak pada menyelesaikan masalah perkalian yang melibatkan hasil tiga digit. Data dikumpulkan melalui observasi sistematis dan dianalisis menggunakan analisis tren visual. Hasil menunjukkan peningkatan yang signifikan dalam akurasi perkalian selama fase intervensi, dengan peningkatan kinerja yang dipertahankan selama tindak lanjut. Temuan ini menyoroti potensi GARISMATIKA sebagai alat pendidikan yang efektif dan inklusif untuk menangani disabilitas pembelajaran matematika tertentu dan mendukung penerapannya yang lebih luas dalam instruksi matematika yang berbeda dalam kelas inklusif.